Modelling humid air flow condensation in a linear blade cascade - Tsymbalyuk Volodymyr; Eret Petr; Slama Vaclav; Rudas Bartolomej; Ira Jiri; Macalka Ales; Peterka Tomas (EPJ Web of Conferences, 2024)
Experimental test rigs such as linear blade cascades often use ambient humid air for internal aerodynamics investigation. However, experimental evidence of flow condensation can be found at higher Mach numbers, especially for lower inlet air temperatures. This paper presents a simple analytical model of the distribution of relative humidity of an air-water mixture and specific mass of condensed vapor as a function of Mach number. Moreover, based on the experimental data, a case study of the transonic flow in a linear blade cascade is performed using ANSYS CFX. The agreement between both approaches is more than satisfactory, leading to further investigations as little is known about the effect of humidity and flow condensation on the flow field.